Os efeitos do trabalho flexível na construção da trajetória profissional do trabalhador contemporâneo - Cuogo, Francisco Coelho (Universidade do Vale do Rio dos Sinos, 2016)
The following dissertation intends to analyze the changes occurred from the 1970s, with the restructuring of capitalism, considering its effects on labor characteristics and on organizational structures impacted by the information society. We intend, therefore, to discuss the changes taking place in the professional context, establishing relations with the transformation of the economy and the organizational context in a transition age, that means from the industrial to the information age. At this scenario, we seek to develop a critical awareness about the demands that have been made by organizations in relation to the skills required of the contemporary worker and how those aspects can affect - positively or negatively - the working class. So we approached in this project the characteristics of the industrial age, narrowing this approach the mechanistic work, fordism characteristics and their effects on taylorism worker. In the following topics, we highlight the Fordist crisis of accumulation, the transition to flexible accumulation, which deal also about Toyotism and informationalism. Next, we consider the effects of neoliberal economics on the characteristics and organization of work, analyzing the stimuli that it gives flexible working. We seek to investigate the consequences of changes in the work of the industrial era (from the perspective of the fordist model) for the information era (from the perspective of flexible accumulation and neoliberalism) on the worker and, more specific, we seek to understand the meanings of such work for the young contemporary worker. To address the characteristics of the fordist model and its effects on the industrial worker we used the Harvey (1992), Alves (1999) and Aranha (2006). When talking about the information society and neoliberalism were analyzed conceptions of Castells (2002) and Anderson (1996) . The aspects related to work - as well as its flexibility - we use as reference the works of Antunes (2005), Sennett (2006) and Lazzarato (2001). We approached also some concepts of management area, as the speech of this area helps to legitimize the work condition at present, especially with regard to flexible working. To support these arguments resorted to authors such as Eboli (2004), Meister (1999) and Caravantes (2008). The research developed in this dissertation raised qualitative data through a questionnaire with open questions. The questionnaires were applied in two professional groups (all in the condition of workers and students in higher education), separated by age group. The first group of young workers were aged 18-35 years and the second group of workers aged above 36 years. Thus, we aim to understand the perception of workers about flexible working. For analysis of the responses to the questionnaire we used the Bardin content analysis method (1994).
Keywords: Fordismo; Industrialização; Informacionalismo; Trabalho flexível; Fordism; Industrialization; Informationalism; Flexible working; ACCNPQ::Ciências Humanas::Sociologia